Carbetocin Versus Oxytocin for Prophylaxis of PPH Used During Caesarean Section: An Open Label Randomized Control Trial (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Postpartum hemorrhage is the leading cause of maternal mortality; uterineatony is the most important cause. Uterotonics are used to prevent uterine atony. Carbetocin,a synthetic anallague of oxytocin seems to be an effective and safe new drug for preventionof PPH after caesareanThe Aim of Study:To find out the efficacy and safety of carbetocin over oxytocin for theprevention of PPH during caesarean section.Patients and Methods: A randomized-controlled trial was conducted in the Dept. of Obs &Gyane, Rangpur Medical College and Hospital, Rangpur, Bangladesh over a period of twelvemonths from June 2016 to June 2017. One hundred admitted patients undergoing cesareansection at term were randomized into two groups receiving either 10 IU oxytocin or 100 μgcarbetocin after caesarean section. Outcome measures such as primary PPH, massiveblood loss, need for additional uterotonic drug, additional blood transfusion as well as adverseeffects were all documented.Results: Massive blood loss occurred in 6% patients, blood transfusion needed in 20% patientsand additional uterotonic needed for 36% patients in Oxytocin group but in Carbetocin groupno massive blood lossoccurred, only 2%patients needed immediate blood transfusion and4% patients were required additional uterotonics. There were no major adverse effectsobserved in both the groups. No patients had developed PPH in carbetocin group. But 8%(4)patients had developed PPH in oxytocin group.Conclusion: Carbetocin appears to be an effective new drug than Oxytocin for the preventionof postpartum hemorrhage following caesarean section.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 113-118